Improved biodegradability and tribological performances of mineral lubricating oil by two synthetic nitrogenous heterocyclic additives. Issue 4 (9th April 2019) - Ding, Jianhua; Fang, Jianhua; Chen, Boshui; Zhang, Nan; Fan, Xingyu; Zheng, Zhe
Abstract : Purpose: This paper aims to understand the influences of tris (2-hydroxyethyl) isocyanurate oleate and oleic acid tris (2-hydroxyethyl) isocyanurate phosphate ester on biodegradability and tribological performances of mineral lubricating oil. Design/methodology/approach: Tris (2-hydroxyethyl) isocyanurate oleate and oleic acid tris (2-hydroxyethyl) isocyanurate phosphate ester were prepared and characterized by Fourier transform infrared spectrometer. The biodegradability and tribological properties of neat oil and its formulations were studied on a tester for fast evaluating biodegradability of lubricants and a four-ball tester, respectively. The worn surfaces were investigated by scanning electron microscope and X-ray photoelectron spectroscope. Findings: Tris (2-hydroxyethyl) isocyanurate oleate and oleic acid tris (2-hydroxyethyl) isocyanurate phosphate ester both improved markedly the biodegradability, the anti-wear properties, friction-reducing properties and extreme pressure properties of base oil. The effect of oleic acid tris (2-hydroxyethyl) isocyanurate phosphate ester was better than tris (2-hydroxyethyl) isocyanurate oleate. The improvement of tribological performances was mainly ascribed to the formation of a complicated boundary lubrication film of tris (2-hydroxyethyl) isocyanurate oleate and oleic acid tris (2-hydroxyethyl) isocyanurate phosphate ester on the friction surfaces. Originality/value: This paper has indicated that tris (2-hydroxyethyl) isocyanurate oleate and oleic acid tris (2-hydroxyethyl) isocyanurate phosphate ester effectively improve the biodegradability and tribological performances of mineral lubricating oil. Promoting biodegradation of mineral lubricant by additives is very significant for the development of petroleum-based biodegradable lubricants. These two additives not merely improve the tribological performances; more importantly, they improve the ecological performances.